Characterization of Ti-25.5Al-13.5Nb-2.8Mo-1.8Fe Alloy Hot Deformation Behavior Through Processing Map - Cheng, Jun; Du, Zhaoxin; Zhang, Xiaoyong; Zhang, Wen; Gai, Jinyang; Li, Jinshan (Frontiers in Materials, 2020)
The isothermal compression tests of Ti-25. 5Al-13.5Nb-2.8Mo-1.8Fe (at.%) alloys were executed under a deformation temperature range of 950–1,100°C with a strain rate range of 0.001–1 s−1 for a total height reduction of 0.5. The isothermal compression deformation behavior was investigated based on flow stress curves and dynamic model analysis. The processing map of the Ti-25.5Al-13.5Nb-2.8Mo-1.8Fe alloy was obtained for the optimum hot process parameters. The calculated value of Q (activation energy) was 634.5 kJ/mol. The constitutive model of the alloy was constructed. Based on DMM and the Prasad flow instability criteria, the hot processing map was established with a strain of 0.7. The deformation mechanisms were interpreted by microstructural observation within both stability and instability zones. A processing map showed a stable region under a deformation temperature range of 950–1,100°C with a strain rate range of 0.001–1 s−1. One certain maximum power dissipation efficiency value was ~43% and occurred at 950°C/0.001 s−1. Another peak power dissipation efficiency value was about 58% at 1,050°C/0.001 s−1. Both areas were the optimum processing regions. Furthermore, while the strain rate value exceeded 1 s−1, the alloy sustained a deformation instability phenomenon, such as a shearing band or flow localization.